EVALUATION OF ANTI-INFLAMMATORY ACTIVITY OF MIMUSOPS ELENGI EXTRACTS IN DIFFERENT IN-VITRO AND IN-VIVO MODELS - DHARMENDRA KUMAR KHATRI; MANJULAKONKA; ARCHANA R JUVEKAR (International Journal of Pharma and Bio Sciences, 2014)
In the present study the anti-inflammatory potential of Methanolic and Aqueous extracts of Leaves of Mimusops elengi L. was evaluated for their in-vitro and in-vivo anti-inflammatory activity. In-vitro anti-inflammatory activity was evaluated by using membrane stabilization assay, proteinase inhibitory activity and immunomodulatory activity using macrophages. In-vivo animal models involve carrageenan induced rat paw edema, in which the decrease in edema formation due to drug treatment (200 and 400 mg/kg) was measured using Plethysmometer and cotton pellet induced granuloma model in which the level of inhibition of granuloma was measured at different dose levels(200 & 400 mg/kg). Methanolic and Aqueous extracts of Mimusops elengi Leaves showed significant results in in-vitro and in-vivo anti-inflammatory models. The results of in-vitro and in-vivo models showed that Mimusops elengi has potential anti-inflammatory activity and acts through multiple mechanisms